Progression of fatigue modifies primary contributors to ground reaction forces during drop landing - Zhang, Q.; Ruan, M.; Singh, N. B.; Huang, L.; Zhang, X.; Wu, X. (Journal of Human Kinetics, 2021)
Few studies have focused on the effect of fatigue severity on landing strategy. This study aimed to investigate the effect of fatigue progression on ground reaction force during landing. Eighteen participants performed a fatigue exercise protocol. Then participants performed drop landings at three levels of fatigue: no fatigue, medium fatigue, and severe fatigue. Multiple linear regression was conducted to identify the predictors of the peak vertical ground reaction force at each level of fatigue. Two-way ANOVAs were conducted to test the effect of fatigue on the vertical ground reaction force and the predictors. For the vertical ground reaction force, the knee joint stiffness and the knee angle at initial contact were the main predictors at no fatigue. The peak knee flexion angle and knee power were the main predictors at medium fatigue. However, the peak ankle plantarflexion moments became the main predictor at severe fatigue. The vertical ground reaction force decreased from no to medium fatigue (p = 0.001), and then increased from medium to severe fatigue (p = 0.034). The knee joint stiffness decreased from no to medium fatigue (p = 0.049), and then remained unchanged from medium to severe fatigue. The peak knee flexion angle increased from no to medium fatigue (p = 0.001), and then slightly decreased from medium to severe fatigue (p = 0.051). The results indicate that fatigue progression causes a transition from stiff to soft landing, and then to stiff landing. Participants used ankle joints more to control the landing intensity at severe fatigue.